Optical Characterization of Neem Leaf by Laser Beam Scanning Spectroscopy (LIBS) and its spectral Properties - Hazim, Noor ALhuda Rafid; Ali, Alyaa Hussein (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2026)
The present investigation is concerned with the spectral characterization by laser-induced bioluminescence spectroscopy (LIBS) of neem (Azadirachta indica) generated plasma, which is one of the most versatile and fast methods for the qualitative and quantitative analysis of various chemical elements, in organic as well as organic materials. Sample excitation and plasma formation were achieved using a pulsed energy laser (50, 100, 150, and 200 mJ). Finally, the emitted spectrum was analyzed in the framework of the Boltzmann and Saha equations for obtaining the plasma temperature and electron density. The influence of the laser power on the spectral parameters, for example, spectral line intensity, electron temperature, and electron density, was investigated, which could contribute to knowing more about the interaction between plasma and the component of the plant sample. The results show that LIBS is a fast and reliable tool for the analysis of chemical elements of the Neem sample, and at the same time, it does not require complex sample preparation, so it is suitable for clinical, pharmacological, and environmental applications. The work demonstrates a direct dependency of the laser power, the associated rise in plasma temperature, and corresponding electron density on the sensitivity of the spectrometer, emphasizing the need to optimize these parameters to achieve accurate and highly repeatable measurements.